Analisis Determinan Faktor yang Mempengaruhi Tingkat Pengangguran Terdidik dengan Teknologi Sebagai Variabel Moderasi di Indonesia - Sinta Ratna Sari; Annis Nurfitriana Nihayah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Indonesia is a country that has a fluctuating number of unemployment and is dominated by education unemployment. This study was to conducted with the aim of analysing the determinants of factors on educated unemployment with technology as a moderating variable in Indonesia in the period 2015-2024. This study uses secondary data obtained from the Central Bureau of Statistics and analysed using panel data regression and Moderated Regression Analysis (MRA) with Eviews 12. The results show that economic growth, education and employment opportunities have a negative and significant effect on educated unemployment. Technology is able to moderate the relationship between economic growth, education and educated unemployment. Technology moderation strengthens the effect of economic growth and employment opportunities on educated unemployment, while technology moderation weakens the effect of education on educated unemployment.